Pengaruh Keadilan Prosedural dan Stres Kerja terhadap Turnover Intention dengan Komitmen Organisasional sebagai Variabel Mediasi pada PT.PJB Services - Wulansari, Yuliana Ayu; Koesmono, Teman; Junaedi, Marliana (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2017)
This research aims to find out and analyze the influence of procedural justice, job stress, organizational commitment and turnover intention on the company's production employees PT PJB Services. This reasearch is quantitative research Technical analysis of the data using the structural equation modeling (SEM). Data obtained from the results of the questionnaire of 175 respondents, by distributing questionnaires to the respondents (production’s employees). The object of reasearch is in PT. PJB Services, that hire employees in production field, selected by using a judgement sampling. The results showed that procedural justice has a positive effect on organizational commitment, then work stress has positive effect on organizational commitment, besides procedural justice has no effect on turnover intention, then work stress has no effect on turnover intention, and organizational commitment has no effect on turnover intention. This result can be seen from the calculation of existing research using LISREL program, through SEM analysis. These results can be seen from the calculation of existing research using LISREL program, through analysis of SEM.